Bioprospective screening and characterization of isolates from Pterocarpus osun leaf and stem bark extracts - Fadeyi, Adewale Elijah; Afolayan, Michael Olalekan; Adeniran, Oluremi Isola (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2023)
Antimicrobial resistance (AMR) ranks among the top 10 world health challenges of the 21st century, predicted that it will cause approximately 10 million deaths in 2050. Therefore, more investigation into identifying new antibiotics from natural sources is inevitable. Compounds from the leaf and stem bark of Pterocarpus osun were isolated using column chromatography, screened for their bioactivities, and characterized using the FTIR spectroscopy method in the ongoing search for novel antimicrobial therapies. The isolates were tested for antibacterial and antifungal activities against eleven pathogenic organisms. The zones of inhibition ranged in diameter from 22 to 30 mm. The minimum inhibitory concentrations were determined. Thin-layer chromatography was used to determine the purity of the compounds, and their retention factor was calculated. This ranged between 0.2424 and 0.8151. The melting points of the compounds were also recorded, as are FTIR spectra ranging from 4000 to 400 cm-1. Some of the peaks recorded are typical of single bond (4000-25000 cm-1), double bond (2000-1500 cm-1) with confirmation in the fingerprint (1500-400 cm-1) region but none in the triple bond (2500-2000 cm-1) region of the spectra. The antimicrobial screening results show that the identified compounds can potentially lead to the discovery of novel antibiotic medications.